Physical exercise as an immunomodulator of chronic diseases in aging - Ciolac, Emmanuel Gomes [UNESP]; da Silva, José Messias Rodrigues [UNESP]; Vieira, Rodolfo Paula (Human Kinetics, 2020)
Background: The progressive dysfunction of the immune system during aging appears to be involved in the pathogenesis of several age-related disorders. However, regular physical exercise can present “antiaging” effects on several physiological systems. Methods: A narrative review of studies investigating the chronic effects of exercise and physical activity on the immune system and its association with age-related chronic diseases was carried out according to the guidelines for writing a narrative review. Results: There is compelling evidence suggesting that age-related immune system alterations play a key role on the pathophysiology of atherosclerosis, hypertension, chronic heart failure, type 2 diabetes, obesity, arthritis, and chronic obstructive pulmonary disease. On the other hand, the regular practice of physical activity appears to improve most of the inflammatory/ immunological processes involved in these diseases. Conclusion: Epidemiological, experimental, and clinical studies permit us to affirm that regular physical activity improves immunomodulation and may play a key role in the prevention and treatment of several age-related chronic diseases. However, further studies are needed to better describe the prophylactic and therapeutic effects of physical exercise in specific organs of older individuals, as well as the mechanisms involved in such response.
Keywords: Cellular response; Elderly; Exercise immunology; Immunomodulation